Dissociation of Pupillary Post-Illumination Responses from Visual Function in Confirmed OPA1 c.983A > G and c.2708_2711delTTAG Autosomal Dominant Optic Atrophy - Nissen, Claus; Rönnbäck, Cecilia; Sander, Birgit; Herbst, Kristina; Milea, Dan; Larsen, Michael; Lund-Andersen, Henrik (Frontiers in Neurology, 2015)
Abstract Purpose: To test whether the melanopsin-containing, intrinsically photosensitive retinal ganglion cells (ipRGCs), as evaluated by examination of the pupillary light reflex (PLR), are preserved in genetically confirmed autosomal dominant optic atrophy (ADOA) Method: 29 patients with either the c.983A>G (n=14) or the c.2708_2711delTTAG mutation (n=15) were examined with monochromatic pupillometry, using isoluminant (300 cd/m2), red (660 nm) or blue (470 nm) light, optical coherence tomography (OCT), automated visual field analysis (VFA), and with determination of best corrected visual acuity (BCVA). Since we examined two different mutations, initially we compared all outcome variables between the two, and finding no statistically significant difference, pooled them. Results: Despite a poor BCVA (56 letters, ETDRS) in the ADOA patients, their post-illuminatory pupil responses did not differ significantly from those of healthy controls (blue, p=0.45, red, p=0.49, t-test), and no statistically significant effect was noted of peripapillary retinal nerve fiber layer thickness, ganglion cell-inner plexiform layer thickness or age. Conclusion: The pupillary light reflex (PLR) to blue light of high luminance (300 cd/m2) was preserved in both c.983A>G and c.2708_2711delTTAG ADOA despite severe visual loss and optic nerve atrophy. The study confirms, in a large study of two genetically homogenous groups, that the the intrinsically photosensitive retinal ganglion cells (ipRGCs) are spared in ADOA.